Testing planets: Institutions tested in an era of uncertainty. (21st April 2020) - Vertesi, Janet
Abstract: Prior accounts of the experimenter's regress in laboratory testing are set against the background of a relatively stable institutional context. Even if the tools are new or the object of investigation is unknown, participating entities are named, a certain degree of funding is presumed, and an organization exists to conduct the test. In this paper, I argue that this background assumption obscures the importance of institutional and organizational context to the sociology of testing. I analyze ethnographic data gathered among a NASA team whose funding is uncertain, whose mission organization is not yet established, and whose object of investigation is inaccessible. In what I characterize as "ontological flexibility, " I reveal how scientists shift their accounts of object agency in response to changes in their institutional environment. As they describe the moon as "uncooperative" or "multiple" while they make appeals to institutions at various stages of support in their exploration projects, this reveals the presence of an "institutional regress": a previously overlooked aspect of the sociology of testing.